Functions of personal relations in business relationship dynamics - Salmi, Asta; Halinen, Aino (Routledge, 2026)
This chapter analyzes the role that personal relations play in the existence and development of business relationships. We revisit the early Halinen and Salmi framework from 2001, discuss it in light of recent research findings, and update it to better reflect the current state of knowledge. We have updated the framework by adopting a more detailed view on relationship development. Essentially, in addition to initiation, ending, and crisis situations, relationship development may include dormant or inactive phases. The revised framework provides a more fine-tuned and situation-based analysis of relationship dynamics. It also extends the examination of personal contacts to include both action-related and cognition-related functions. We pay attention to the embeddedness aspect: The dynamics of business relationships depend on a variety of personal relations and networks in which business relationships are inevitably embedded. Furthermore, we suggest the sensemaking perspective as a relevant approach to studying the role of personal relations in situations of major change.
Individuals in B2B Marketing : Sensemaking and Action in Context